Executive control in language production by children with and without language impairment. Issue 4 (28th March 2019) - Sikora, Katarzyna; Roelofs, Ardi; Hermans, Daan; Knoors, Harry
Abstract: Background: Accumulating evidence suggests that the updating, inhibiting and shifting abilities underlying executive control are important for spoken language production in adults. However, little is known about this in children. Aims: To examine whether children with and without language impairment differ in all or only some of these executive abilities, and whether they show corresponding differences when these abilities are engaged in language production. Methods & Procedures: Thirty‐three children with specific language impairment (SLI) and 41 typically developing (TD) children (age matched, aged 8–12 years) completed standard executive control tests that measure the updating, inhibiting and shifting abilities. All children were native speakers of Dutch. Moreover, they performed a noun–phrase production task involving picture description within a picture–word interference paradigm. We measured their production accuracy and speed to assess length, distractor and switch effects, which reflect the updating, inhibiting and shifting abilities underlying executive control. Outcomes & Results: Compared with TD children, the children with SLI had lower scores on all executive control tests. Moreover, they were overall slower and made more errors in the noun–phrase production task. Additionally, the magnitude of the distractor and switch effects was larger for the SLI than for the TD group. Conclusions & Implications: The results suggest that children with SLI have impaired language production and executive control abilities, and that some of the differences in the executive control abilities between SLI and TD groups were reflected in their language production.